Video-Assisted Thoracoscopic Segmentectomy for Deep and Peripheral Small Lung Cancer - Takamori, Satoshi; Oizumi, Hiroyuki; Suzuki, Jun; Suzuki, Katsuyuki; Kabasawa, Takanobu (The Thoracic and Cardiovascular Surgeon, 2021)
Background We aimed to retrospectively compare the long-term prognosis and recurrence after segmentectomy between nonsmall cell lung cancer (NSCLC) patients with deep and peripheral lesions.Methods Data were extracted for 85 lobectomy-tolerable NSCLC patients with tumors measuring ≤2 cm, who underwent video-assisted thoracoscopic segmentectomy with curative intent during January 2006 to December 2014. Tumor location was determined by the surgeon using thin-slice (1 mm) and three-dimensional computed tomography. Overall and recurrence-free survival was compared between patients with peripheral and deep lesions using univariate and multivariate Cox proportional hazard models. The indications for segmentectomy included NSCLC measuring ≤2 cm and consolidation/tumor ratio ≤20%, solid NSCLC ≤1 cm, and indeterminate nodule ≤1.5 cm.Results No recurrence of peripheral and deep lesions was noted. The 5-year overall survival was 96.4% for all patients, and 100 and 95.3% for patients with deep and peripheral lesions, respectively. There was no significant difference between the overall survival rates associated with the deep and peripheral lesions (95% confidence interval [CI], 89.5–98.8, nonsignificant, 86.4–98.4, respectively; p = 0.189). In a multivariate analysis, the American Society of Anesthesiologists score (hazard ratio [HR], 13.30; 95% CI, 1.31–210.36; p = 0.028) and histology (HR, 0.03; 95% CI, 0.00–0.32; p = 0.037) were independent prognostic factors for overall survival; tumor location was not a prognostic factor.Conclusions When video-assisted thoracoscopic segmentectomy with curative intent was performed with sufficient surgical margins, the location of small NSCLC did not affect recurrence risk and prognosis. Video-assisted thoracoscopic segmentectomy for small NSCLC is acceptable, regardless of the tumor location.
Keywords: small/VATS; lung cancer; outcomes